Electronic brachytherapy for superficial and nodular basal cell carcinoma: a report of two prospective pilot trials using different doses - Ballester-Sánchez, Rosa; Pons-Llanas, Olga; Candela-Juan, Cristian; Celada-Álvarez, Francisco Javier; A. Barker, Christopher; Tormo-Micó, Alejandro; Pérez-Calatayud, Jose; Botella-Estrada, Rafael (Journal of Contemporary Brachytherapy, 2016)
Purpose : Basal cell carcinoma (BCC) is a very common cancer in the Caucasian population. Treatment aims to eradicate the tumor with the lowest possible functional and aesthetic impact. Electronic brachytherapy (EBT) is a treatment technique currently emerging. This study aims to show the outcomes of two consecutive prospective pilot clinical trials using different radiation doses of EBT with Esteya® EB system for the treatment of superficial and nodular basal cell carcinoma. Material and methods : Two prospective, single-center, non-randomized, pilot studies were conducted. Twenty patients were treated in each study with different doses. The first group (1) was treated with 36.6 Gy in 6 fractions of 6.1 Gy, and the second group (2) with 42 Gy in 6 fractions of 7 Gy. Cure rate, acute toxicity, and late toxicity related to cosmesis were analyzed in the two treatment groups. Results: In group 1, a complete response in 90% of cases was observed at the first year of follow-up, whereas in group 2, the complete response was 95%. The differences with reference to acute toxicity and the cosmetic results between the two treatment groups were not statistically significant. Conclusions : Our initial experience with Esteya® EB system to treat superficial and nodular BCC shows that a dose of 36.6 Gy and 42 Gy delivered in 6 fraction of 7 Gy achieves a 90% and 95% clinical cure rate at 1 year, respectively. Both groups had a tolerable toxicity and a very good cosmesis. The role of EBT in the treatment of BCC is still to be defined. It will probably become an established option for selected patients in the near future.